High-mechanical-strength wide-temperature low-loss manganese-zinc ferrite, preparation method and application thereof

CN122878124APending Publication Date: 2026-10-09ZHEJIANG TIANTONG ELECTRONIC INFORMATION MATERIALS RESEARCH INSTITUTE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611100307.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]然而,现有文献主要关注Bi2O3和WO3各自对磁导率或烧结性能的单一影响

Benefits of technology

(1)通过添加Bi2O3作为助溶剂,形成液相促进烧结,降低孔隙率,提高铁氧体密度;WO3偏析于晶界,W6+凭借其高电荷会引起强烈的局部晶格畸变,加速固相反应,并与Bi2O3形成复合相,显著增强晶界结合力,使抗弯强度获得大幅提升;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878124A_ABST
    Figure CN122878124A_ABST
Patent Text Reader

Abstract

The application belongs to the field of magnetic materials, and discloses a high-mechanical-strength wide-temperature-range low-loss manganese-zinc ferrite as well as a preparation method and application thereof. The preparation method comprises the following steps: weighing main components Fe2O3, ZnO and MnO according to a proportion, ball milling to obtain uniform mixed materials, pre-sintering, and obtaining active spinel structure MnZn ferrite pre-sintered materials after reaction; adding auxiliary components, ball milling to obtain uniform powder; adding a binder to granulate, baking to obtain granular materials, and pressing into green bodies; and low-temperature sintering to obtain manganese-zinc ferrite. The auxiliary components comprise Bi2O3 and WO3. The manganese-zinc ferrite prepared by the method can significantly improve the bending strength of the material while realizing the characteristics of low power loss in a wide temperature range (25 DEG C to 120 DEG C).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of magnetic materials, particularly the field of soft magnetic ferrite material preparation, and specifically relates to a manganese-zinc ferrite with high mechanical strength, wide temperature range and low loss characteristics, as well as its preparation method and application. Background Technology

[0002] As power supplies for new energy vehicles, 5G communication base stations, and cloud computing servers develop towards higher power density, miniaturization, and higher reliability, more stringent performance requirements are being placed on manganese-zinc (MnZn) ferrite, the core material for power magnetic components. Especially in applications such as on-board chargers (OBCs) and DC-DC converters, the magnetic core not only needs to maintain low power loss (Pcv) over a wide temperature range of -40℃ to 120℃ to reduce its own heat generation, but also must possess excellent mechanical strength to resist assembly stress and long-term vibration and shock.

[0003] To improve the mechanical strength of manganese-zinc ferrites, numerous technological explorations have been undertaken. Chinese patent CN202511702474.5 discloses a high-mechanical-strength, high-magnetic-induction manganese-zinc ferrite material. By adding auxiliary components such as SiO2, CaO, and V2O5 to the main component and limiting the mass ratio of SiO2 to CaO and CaO to V2O5, a uniform and fine grain structure is formed during sintering, thus achieving a balance between mechanical strength and high magnetic induction. Chinese patent CN202511887594.7, by adding auxiliary components such as nano-yttrium iron garnet (YIG), CaSiO3, Nb2O5, Ho2O3, and Co2O3 to the formulation, reduces eddy current loss while improving bending strength, achieving a balance between high bending strength and low high-frequency loss. The above technical solutions mainly enhance grain boundary bonding through methods such as the CaO-SiO2 grain boundary glass phase and the Nb2O5 / ZrO2 grain boundary pinning effect, thereby improving the mechanical properties of the material to a certain extent. However, these solutions often focus on optimizing a single performance indicator and lack a systematic solution for balancing mechanical strength and wide-temperature, low-loss characteristics.

[0004] Bi₂O₃, due to its low melting point (approximately 825℃), can form a liquid phase during sintering, promoting particle rearrangement and densification. It is often used as a sintering aid in the preparation of high-permeability MnZn ferrite materials. Related patents (such as patent publication number CN119430899A) have included it as an auxiliary component in manganese-zinc ferrite, increasing the permeability by 10%. WO₃, as a high-valence metal oxide, has also been reported in the application of MnZn ferrite. Studies have shown that an appropriate amount of WO₃ can promote grain growth within a certain range, which is beneficial for improving permeability. 6+ Ions entering the spinel lattice can modulate Fe 2+ / Fe 3+The ratio affects the resistivity and loss characteristics of the material (see patent publication number CN104761249A).

[0005] However, existing literature mainly focuses on the individual effects of Bi2O3 and WO3 on magnetic permeability or sintering performance. This invention aims to prepare a manganese-zinc ferrite that combines high mechanical strength with wide temperature range and low loss characteristics. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a high-mechanical-strength, wide-temperature-range, low-loss manganese-zinc ferrite, its preparation method, and its application. The manganese-zinc ferrite prepared by this method significantly improves the bending strength of the material while achieving low power loss over a wide temperature range (25℃~120℃).

[0007] The purpose of this invention is to provide a method for preparing high-mechanical-strength, wide-temperature-range, low-loss manganese-zinc ferrite, comprising the following steps: (1) Preparation of MnZn pre-calcined material: The main components Fe2O3, ZnO and MnO are weighed according to the ratio, ball milled to obtain a uniform mixture, pre-calcined at a pre-calcination temperature of 800~900℃, the pre-calcination atmosphere is air, cooled, and after the reaction, an active spinel structure MnZn ferrite pre-calcined material is obtained. (2) Ball milling: Add auxiliary components to the pre-burned material obtained in step (1), and ball mill to obtain uniform powder; (3) Granulation and pressing: Add binder to the powder obtained in step (2) for granulation, bake, and obtain granules with uniform size and good flowability, and press them into green bodies; (4) Sintering: The green body pressed in step (3) is sintered at low temperature to obtain manganese zinc ferrite; In step (2), the auxiliary components include Bi2O3 and WO3. 3, Based on the total weight of the main components Fe2O3, ZnO and MnO, the amount of Bi2O3 used is 1~600 ppm, and the amount of WO3 used is 1~100 ppm.

[0008] This method introduces Bi2O3 and WO3 auxiliary components. The low melting point of Bi2O3 promotes densification, while WO3 enhances grain boundary strength. In this invention, Bi2O3 and WO3 mainly segregate at the grain boundaries, which significantly improves the bending strength of the material while ensuring low power loss over a wide temperature range.

[0009] The core of the technical solution of this invention lies in the fact that Bi2O3, with its low melting point (about 825°C), forms a low-viscosity liquid phase at the grain boundaries during sintering, which promotes particle rearrangement and the expulsion of pores, significantly improving the material density. According to Griffith's theory of microcrack texture, the reduction of defects such as pores is the key to improving the strength of ceramics. At the same time, Bi2O3 segregates in the grain boundary region, effectively enhancing the intergranular bonding force, making it difficult for cracks to propagate along the grain boundaries.

[0010] Secondly, the introduction of WO3 has multiple enhancing effects: W 6+ Ions enter the spinel lattice and replace Fe. 3+ The difference in ion size and valence state causes lattice distortion, which hinders dislocation movement and increases the intrinsic hardness of the material. At the same time, WO3 segregates at the grain boundaries to form pinning centers, which inhibits abnormal grain growth and refines the microstructure. More importantly, Bi2O3 and WO3 form a composite phase (such as Bi2WO3) at the grain boundaries, which produces a double pinning effect on the grain boundaries, significantly enhancing the grain boundary bonding force and greatly improving the bending strength.

[0011] This invention utilizes the synergistic effect of Bi2O3 and WO3 combined with a low-temperature sintering process to develop a wide-temperature, low-loss MnZn ferrite material while significantly improving the mechanical strength of manganese-zinc ferrite.

[0012] In this invention, the amount of Bi2O3 and WO3 added is relatively small, which further reduces the impact on magnetic properties and further ensures that the material has a wide temperature range and low loss while improving mechanical strength.

[0013] Furthermore, in step (1), the amounts of the main components are as follows: Fe2O3: 51.0~54.0 mol%, ZnO: 9.0~12.0 mol%, and the remainder is MnO.

[0014] Further, in step (3), the binder is polyvinyl alcohol (PVA), the amount of binder is 12-15 wt% of the powder, and it is baked at 110-130℃ for 9-10 minutes. The pressing force of the green body is 15-17 tons.

[0015] Furthermore, in step (4), the low-temperature sintering holding temperature is 1150~1220℃, the holding time is 3~6h, the sintering atmosphere is carried out under balanced oxygen partial pressure, and the holding oxygen content is set to 3.5~4.2 vol.

[0016] Furthermore, in step (2), the auxiliary components also include at least one of CaCO3, Nb2O5, Co2O3, SiO2, and V2O5. Preferably, based on the total weight of the main components Fe2O3, ZnO, and MnO, the amounts used are as follows: CaCO3: 100~500 ppm, Nb2O5: 100~400 ppm, Co2O3: 1000~3000 ppm, SiO2: 50~200 ppm, and V2O5: 100~400 ppm. CaCO3, SiO2, Nb2O5, etc., together construct a high-resistivity grain boundary layer, further reducing eddy current losses and ensuring wide-temperature low-loss ferrite.

[0017] Furthermore, in step (2), the ball milling speed is 250-350 rpm to obtain the final powder D. 50 : 1.1~1.4μm.

[0018] Furthermore, in step (3), after granulation, the particles are sieved through 60-mesh and 120-mesh sieves to remove large and small particles and improve the size uniformity, flowability and bulk density of the powder.

[0019] Furthermore, in step (3), the density of the pressed green body is controlled at 2.9~3.1 g / cm³. 3 .

[0020] The present invention also aims to provide a high mechanical strength, wide temperature range, and low loss manganese-zinc ferrite prepared by the above preparation method.

[0021] Another objective of this invention is the application of the aforementioned manganese-zinc ferrite in on-board chargers (OBCs) or DC-DC converters. The manganese-zinc ferrite of this invention maintains low power loss (Pcv) over a wide temperature range of -40°C to 120°C, and possesses excellent mechanical strength to resist assembly stress and long-term vibration shock.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) By adding Bi2O3 as a co-solvent, a liquid phase is formed to promote sintering, reduce porosity, and increase ferrite density; WO3 segregates at grain boundaries, W 6+ Its high charge causes strong local lattice distortion, accelerates solid-state reaction, and forms a composite phase with Bi2O3, which significantly enhances grain boundary bonding and greatly improves bending strength. (2) The manganese-zinc ferrite prepared by this invention has a bending strength of 75~95 MPa, which is more than 30% higher than that of the comparative example without Bi2O3-WO3; and the power loss Pcv at 100 kHz / 200 mT is ≤280kW / m in a wide temperature range of 25℃~120℃. 3 (25℃) and ≤330 kW / m3 (120℃), saturation magnetic induction intensity Bs≥ 520 mT (25℃), fully meeting the requirements of high-end applications.

[0023] In summary, by introducing Bi2O3 and WO3 auxiliary components, the present invention utilizes the low melting point of Bi2O3 to promote densification, while WO3 enhances grain boundary strength. The manganese-zinc ferrite prepared by this method significantly improves the bending strength of the material and achieves low power loss over a wide temperature range (25℃~120℃). Attached Figure Description

[0024] Figure 1 Here is a SEM image of MnZn ferrite. Figure 1 (a) is a cross-sectional view of the MnZn ferrite without Bi2O3 and WO3 doping in Comparative Example 1. Figure 1 (b) is a cross-sectional view of the MnZn ferrite doped with 300 ppm Bi2O3 and 50 ppm WO3 in Example 2; Figure 2 (a) is the Vickers hardness diagram of Comparative Example 1 without Bi2O3 and WO3 doping. Figure 2 (b) Vickers hardness diagram of MnZn ferrite doped with 300 ppm Bi2O3 and 50 ppm WO3 in Example 2. Detailed Implementation

[0025] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0026] The present invention aims to solve the technical problem of the difficulty in achieving both mechanical strength and wide-temperature low-loss characteristics in manganese-zinc ferrite materials in the prior art, and provides a high-strength, wide-temperature low-loss manganese-zinc ferrite and its preparation method.

[0027] This method introduces Bi₂O₃ and WO₃ as auxiliary components. Bi₂O₃'s low melting point promotes densification, while WO₃ enhances grain boundary strength. This significantly improves the material's flexural strength while ensuring low power loss over a wide temperature range. The core of this invention lies in the fact that Bi₂O₃, with its low melting point (approximately 825°C), forms a low-viscosity liquid phase at grain boundaries during sintering, promoting particle rearrangement and pore expulsion, significantly increasing material density. According to Griffith's microcrack theory, reducing defects such as pores is key to improving ceramic strength. Simultaneously, Bi₂O₃ segregates in the grain boundary region, effectively enhancing intergranular bonding and making crack propagation along grain boundaries difficult. Furthermore, the introduction of WO₃ produces multiple strengthening effects: W… 6+ Ions enter the spinel lattice and replace Fe. 3+ The difference in ion size and valence state causes lattice distortion, hindering dislocation movement and increasing the intrinsic hardness of the material. Simultaneously, WO3 segregates at grain boundaries to form pinning centers, inhibiting abnormal grain growth and refining the microstructure. More importantly, Bi2O3 and WO3 may form a composite phase (such as Bi2WO3) at grain boundaries, producing a dual pinning effect on the grain boundaries, significantly enhancing grain boundary bonding and resulting in a substantial increase in flexural strength. On the other hand, Bi2O3 and WO3 mainly segregate at grain boundaries, and their addition amounts are relatively small, having little impact on magnetic properties. This allows for improved mechanical strength while maintaining a wide temperature range and low loss.

[0028] Specifically, the technical solution of the present invention is as follows: A method for preparing high mechanical strength, wide temperature range, and low loss manganese-zinc ferrite includes the following steps: Step 1: Preparation of MnZn pre-calcined material The main components Fe2O3, ZnO, and MnO were proportioned according to the measured amounts of each component. A wet-mixing process was used, followed by a single ball milling to obtain a homogeneous slurry. After drying and pulverizing, the slurry was pre-fired at 800-900℃ in an air atmosphere, and cooled with the furnace. The resulting product was an active spinel-structured MnZn ferrite pre-fired material.

[0029] Step 2, ball milling Add the designed amount of auxiliary components to the pre-calcined material prepared in step (1), add and mix according to the mass ratio of deionized water to raw material 1:1, wet ball mill for 20~30 min, and dry to obtain powder.

[0030] Step 3, Granulation and Compression The PVA obtained in step (2) with 12-15% added was granulated and sieved, and baked at 120℃ for 9-10 minutes to obtain granules with uniform size and good flowability. The granules were then bidirectionally pressed into 25×15×7.5mm green rings and 70×15×5mm rectangular green bodies using a 16-ton press.

[0031] Step 4, Sintering The green ring pressed in step (3) is placed into a bell furnace for low-temperature sintering. The sintering temperature is 1150~1220℃ and the holding time is 3~6h. The sintering atmosphere is under balanced oxygen partial pressure and the holding oxygen content is set to 3.5~4.2vol.

[0032] Furthermore, as a preferred embodiment, based on the total weight of the main components Fe2O3, ZnO, and MnO as 100%, the amount of auxiliary components added is: 100~500 ppm CaCO3, 100~400 ppm Nb2O5, 1000~3000 ppm Co2O3, 50~200 ppm SiO2, 100~400 ppm V2O5, 0~600 ppm Bi2O3, and 0~100 ppm WO3.

[0033] Preferably, in step 2, the ball milling speed is 300 rpm, and the final powder D 50 : 1.1~1.4μm.

[0034] Preferably, in step 4, the powder is sieved through 60-mesh and 120-mesh sieves to remove large and small particles, improve the size uniformity, flowability, and bulk density of the powder, and control the density of the pressed green ring to 2.9~3.1 g / cm³. 3 .

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a method for preparing high-mechanical-strength, wide-temperature-range, low-loss manganese-zinc ferrite. By adding Bi₂O₃ as a co-solvent, a liquid phase is formed to promote sintering, reduce porosity, and increase ferrite density. WO₃ segregates at the grain boundaries. 6+ Its high charge causes strong local lattice distortion, accelerates solid-state reactions, and forms a composite phase with Bi2O3, significantly enhancing grain boundary bonding and greatly improving bending strength. CaCO3, SiO2, and Nb2O5 together construct a high-resistivity grain boundary layer, reducing eddy current losses and ensuring wide-temperature low-loss ferrite.

[0036] The manganese-zinc ferrite prepared by this invention has a bending strength of 75-95 MPa, which is more than 30% higher than that of the comparative sample without Bi2O3-WO3. Within a wide temperature range of 25℃ to 120℃, the power loss Pcv at 100 kHz / 200 mT is ≤280 kW / m. 3 (25℃) and ≤330 kW / m 3 (120℃), saturation magnetic induction intensity Bs≥ 520 mT (25℃), fully meeting the requirements of high-end applications.

[0037] Examples 1-6 Prepare the sample according to the following steps.

[0038] (1) Preparation of MnZn pre-calcined material: The materials were weighed according to the following proportions: 53.2 mol% Fe2O3, 10.5 mol% ZnO and 36.3 mol% MnO. After one wet ball milling (300 rpm, 10 min), a uniform slurry was obtained. After drying and pulverizing, it was pre-calcined at 850℃ for 2 h in an air atmosphere. The furnace was cooled. After the reaction, MnZn ferrite pre-calcined material with active spinel structure was obtained.

[0039] (2) Ball milling: Add the designed amount of auxiliary components to the pre-calcined material prepared in step (1). Based on the total weight of the main components Fe2O3, ZnO, and MnO as 100%, the amounts are: CaCO3: 300 ppm, Nb2O5: 200 ppm, Co2O3: 2000 ppm, SiO2: 100 ppm, and V2O5: 200 ppm. Examples 1-6 were respectively prepared by adding deionized water at a ratio of 1:1 (Bi2O3 and WO3 by mass percentage as shown in Table 1) to the raw materials, and then wet ball milling for 20 min at 300 rpm. After drying in a 120℃ drying oven for 4 h, dry powder was obtained.

[0040] (3) Granulation and pressing: The powder obtained in step 2 was crushed and sieved, and then 15% PVA (by weight of the crushed powder) was added for granulation. After passing through 60-mesh and 120-mesh sieves to remove large and small particles, the powder was dried at 120℃ for 9.5 min to obtain uniformly sized and free-flowing granules. These granules were then bidirectionally pressed into 25×15×7.5 mm green rings and 70×15×5 mm rectangular green bodies using a 16-ton press. The green body density was 3.0 g / cm³. 3 The ring is used to test electromagnetic properties, and the cuboid sample is used to test bending strength.

[0041] (4) Sintering: The pressed green ring obtained in step 3 is placed into a bell furnace for sintering. The sintering temperature is 1200℃ and the holding time is 3 h. Sintering is carried out under balanced oxygen partial pressure and the oxygen content in the holding section is 4.0 vol.

[0042] Comparative Examples 1-3 Compared with Examples 1-6, Comparative Example 1 did not add Bi2O3 and WO3, Comparative Example 2 did not add WO3 and the amount of Bi2O3 was 300 ppm, Comparative Example 3 did not add Bi2O3 and the amount of WO3 was 100 ppm, and the rest of the preparation methods were the same.

[0043] Performance testing The cuboid samples obtained by the above steps in Examples 1-6 and Comparative Examples 1-3 were subjected to bending strength tests.

[0044] The sample rings prepared by the above steps in Examples 1-6 and Comparative Examples 1-3 were tested for power consumption Pcv, saturation flux density Bs, and initial permeability μi on the SY8218 instrument of Iwasaki Corporation, Japan. The test conditions were as follows: Pcv was tested at 100 kHz and 200 mT; Bs was tested at 1 kHz and 1194 A / m. The performance is recorded in Table 1 below.

[0045] Test method: initial permeability μ i Tested using an LCR meter at 10 kHz and 5 mV.

[0046] Saturation magnetic flux density Bs and power loss Pcv: Power consumption Pcv, saturation magnetic flux density Bs, and initial permeability μ were measured using a SY8218 instrument from Iwasaki Corporation, Japan. i The tests were conducted under the following conditions: Pcv was tested at 100 kHz and 200 mT; Bs was tested at 1 kHz and 1194 A / m.

[0047] Bending strength: Using a universal testing machine, three-point bending method, span 30 mm, compressive rate 0.5 mm / min.

[0048] Density: Archimedes' displacement method was used.

[0049] Table 1. Formulation and performance test results of each comparative example and embodiment.

[0050] As shown in Table 1, the flexural strength data indicates that adding Bi2O3 alone (Comparative Example 2, 300 ppm) only slightly increased the strength from 55 MPa to 59 MPa, while adding WO3 alone (Comparative Example 3, 100 ppm) increased it to 63 MPa. The reinforcing effect of either alone is limited.

[0051] The flexural strength was significantly improved after the combined addition of Bi2O3 and WO3. With a fixed Bi2O3 content of 300 ppm, increasing the WO3 content from 0 to 50 ppm (Example 2) resulted in a strength increase from 59 MPa to 85 MPa, a 44% increase; further increasing it to 100 ppm (Example 5) yielded a strength of 89 MPa, a 62% improvement over Comparative Example 1. At a Bi2O3 content of 450 ppm, the flexural strength of Example 6 reached 90 MPa, the highest among all samples. Density showed a slight increase with increasing Bi2O3 content. The Vickers hardness data and flexural strength exhibited good consistency, further verifying the synergistic enhancement effect of the combined addition of Bi2O3 and WO3 on the material's mechanical properties. Comparative Example 1 (without additives) had a Vickers hardness of 566, and the hardness showed a significant upward trend with the introduction of Bi2O3 and WO3. Figure 2 This is the Vickers hardness diagram for MnZn ferrite. Figure 2 (a) is the Vickers hardness chart of the comparative examples without Bi2O3 and WO3 doping. Figure 2 (b) Vickers hardness diagram of Example 2 with 300 ppm Bi2O3 and 50 ppm WO3.

[0052] Bi2O3 forms a low-melting-point liquid phase during sintering, promoting grain rearrangement and densification, while the addition of WO3, on the one hand, promotes grain rearrangement and densification. 6+ Ions entering the crystal lattice cause lattice distortion, increasing the grain boundary bonding force; on the other hand, WO3 and Bi2O3 may form a composite phase (such as Bi2WO6) at the grain boundary, further strengthening the grain boundary, thus producing a reinforcement effect far greater than that of a single additive.

[0053] The loss data in the table show that adding a small amount of WO3 has no significant effect on ferrite loss. The losses in Examples 1 and 2, with WO3 addition of 50 ppm, are: 261~262 kW / m³ at 25℃. 3 Loss at 100℃ is 323~325kW / m 3 Compared to Comparative Example 1, the loss performance was very close. However, in Example 3, when the Bi₂O₃ content reached 450 ppm, the loss showed a slight deterioration. Examples (4-6) with WO₃ addition of 100 ppm: loss at 25°C 272-294 kW / m². 3 At 100℃, the power loss is 352~367 kW / m. 3 Compared to Comparative Example 1, the loss increased by 34~49 kW / m at 100℃. 3 (Approximately 10.7%~15.4%), the deterioration trend accelerated significantly, especially when Bi2O3 was also high (Example 6, loss reached 367 kW / m³ at 100°C).

[0054] Figure 1 Here is a SEM image of MnZn ferrite, where Figure 1 (a) is a cross-sectional structure diagram of MnZn ferrite without Bi2O3 and WO3 in Comparative Example 1; Figure 1 (b) is a cross-sectional structure diagram of MnZn ferrite doped with 300 ppm Bi₂O₃ and 50 ppm WO₃; the red solid circles in the diagram represent grain fracture interfaces. From Figure 1 (a) As can be seen, in the fracture surface of Comparative Example 1 sample without Bi2O3 and WO3, the cracks mainly propagate along the grain boundaries, exhibiting typical intergranular fracture characteristics, with smooth grain surfaces visible on the fracture surface. This indicates that the grain boundary bonding strength of the undoped sample is relatively weak, the cracks preferentially propagate along the grain boundaries, the fracture path is relatively straight, and less fracture energy is consumed, resulting in a lower macroscopic bending strength (only 55 MPa). Figure 1 (b) It can be seen that the fracture mode of the sample from Example 2 with 300 ppm Bi₂O₃ and 50 ppm WO₃ added underwent a significant change—the proportion of transgranular fracture increased significantly, with a large number of cracks penetrating the interior of the grains, and grain cleavage planes and river patterns visible on the fracture surface. This phenomenon indicates that the combined addition of Bi₂O₃ and WO₃ effectively strengthens the grain boundaries: WO₃ segregates at the grain boundaries and forms a composite phase with Bi₂O₃, greatly improving the grain boundary bonding strength. When cracks propagate, they are difficult to extend along the strengthened grain boundaries and are forced to penetrate the interior of the grains. The transgranular fracture path is longer and more tortuous, consuming more fracture energy, thus significantly improving the macroscopic flexural strength (reaching 85 MPa in Example 2, a 55% increase compared to Comparative Example 1).

[0055] Therefore, when 300 ppm of Bi2O3 and 50 ppm of WO3 are added, the addition of Bi2O3 and WO3 optimizes the mechanical strength of manganese zinc ferrite, while the wide temperature loss does not deteriorate significantly and remains at a low level.

[0056] In summary, by introducing Bi2O3 and WO3 auxiliary components, the present invention utilizes the low melting point of Bi2O3 to promote densification, while WO3 enhances grain boundary strength. The manganese-zinc ferrite prepared by this method significantly improves the bending strength of the material and achieves low power loss over a wide temperature range (25℃~120℃).

[0057] The above embodiments are for illustrative purposes only and are not intended to limit the invention. Those skilled in the art can make various changes or modifications without departing from the spirit and scope of the invention. Therefore, all equivalent technical solutions should also fall within the scope of the invention and should be defined by the claims.

Claims

1. A method for preparing high mechanical strength, wide temperature range, and low loss manganese-zinc ferrite, characterized in that, Includes the following steps, (1) Preparation of MnZn pre-calcined material: The main components Fe2O3, ZnO and MnO are weighed according to the ratio, ball milled to obtain a uniform mixture, pre-calcined at a pre-calcination temperature of 800~900℃, the pre-calcination atmosphere is air, cooled, and after the reaction, an active spinel structure MnZn ferrite pre-calcined material is obtained. (2) Ball milling: Add auxiliary components to the pre-burned material obtained in step (1), and ball mill to obtain uniform powder; (3) Granulation and pressing: Add binder to the powder obtained in step (2) for granulation, bake, and obtain granules with uniform size and good flowability, and press them into green bodies; (4) Sintering: The green body pressed in step (3) is sintered at low temperature to obtain manganese zinc ferrite; In step (2), the auxiliary components include Bi2O3 and WO3. The amount of Bi2O3 is 1~600 ppm and the amount of WO3 is 1~100 ppm, based on the total weight of the main components Fe2O3, ZnO and MnO.

2. The preparation method according to claim 1, characterized in that, In step (1), the amounts of the main components are as follows: Fe2O3: 51.0~54.0 mol%, ZnO: 9.0~12.0 mol%, and the remainder is MnO.

3. The preparation method according to claim 1, characterized in that, In step (4), the low-temperature sintering holding temperature is 1150~1220℃, the holding time is 3~6h, the sintering atmosphere is under balanced oxygen partial pressure, and the holding oxygen content is set to 3.5~4.2 vol.

4. The preparation method according to claim 1, characterized in that, In step (3), the binder is polyvinyl alcohol (PVA), the amount of binder is 12-15 wt% of the powder, and it is baked at 110-130℃ for 9-10 minutes. The pressing force of the green body is 15-17 tons.

5. The preparation method according to claim 1, characterized in that, In step (2), the auxiliary components also include at least one of CaCO3, Nb2O5, Co2O3, SiO2, and V2O5; based on the total weight of the main components Fe2O3, ZnO, and MnO, their amounts are respectively CaCO3: 100~500 ppm, Nb2O5: 100~400 ppm, Co2O3: 1000~3000 ppm, SiO2: 50~200 ppm, and V2O5: 100~400 ppm.

6. The preparation method according to claim 1, characterized in that, In step (2), the ball milling speed is 250-350 rpm, and the final powder D is obtained. 50 : 1.1~1.4μm; In step (3), after granulation, the particles are sieved through 60 mesh and 120 mesh screens respectively.

7. The preparation method according to claim 1, characterized in that, The density of the pressed green body is controlled between 2.9 and 3.1 g / cm³. 3 .

8. A manganese-zinc ferrite with high mechanical strength, wide temperature range, and low loss, prepared by the preparation method according to any one of claims 1-7.

9. The application of the manganese-zinc ferrite as described in claim 8 in on-board chargers (OBC) or DC-DC converters.

Citation Information

Patent Citations

  • Manganese zinc ferrite material and preparation method thereof

    CN104761249A

  • Manganese zinc ferrite material as well as preparation method and application thereof

    CN119430899A

  • Manganese zinc ferrite material with high mechanical strength and high magnetic induction as well as preparation method and application of manganese zinc ferrite material

    CN121449414A

  • High-mechanical-property low-loss high-frequency manganese-zinc power ferrite and preparation method thereof

    CN121573971A